Development and Its Discontents: The Story of a Janus-faced Concept. (January 2014) - Zutshi, Somnath
The word 'development' is at the same time both 'concrete' as well as 'contentious'. It is subject to the historic contexts determined by prevailing ideology of the period. The attempt is to focus on the post-World War II period. In this period, the word 'development' has also come into its own with accompanying words such as 'modernization'. The present phase of neo-liberalism has its historic roots in evolving dominant consensus following the 1929 depression. From Keynesian economics to Bretton Woods, to the advent of deregulation policies of Reaganomics and Thatcherism, this article would be a metaphorical and theoretical exploration to the idea of 'development'.